THE IMPLEMENTATION OF THE 21TH CENTURY COMPETENCY FOR ELEMENTARY SCHOOL TEACHERS AT CURRICULUM 2013 TRAINING CENTRAL JAVA PROVINCE YEAR 2017 - Mulida Hadrina Harjanti (Universitas Sebelas Maret, 2018)
The purpose of writing this paper is; 1) to understand methods and strategies in applying 21st century competency (4C = critical thinking, creative thinking, communication, and collaborative) and; 2) to show the results of the competence of 21st century elementary school teachers in training curriculum 2013. The method used in this research is descriptive qualitative method. The results and discussion of this paper is the strategy of training in the application of 21st century competence and Strengthening Character Education. first teacher show and give exemplary to the character and competence of the 21st century. The role of teachers as examples must be highlighted. If you want to teach the character, then the teacher must first display their character. While the results of the application of 21st century competence and Strengthening Character Education after the 2013 curriculum training can be shown by increasing the achievement of the quality report cards on the competency standards of graduates, content, process, and assessment standards.